Opting out : the story of the parents' grassroots movement to achieve whole-child public schools - Hursh, David W., 1948-; Deutermann, Jeanette; Rudley, Lisa; Chen, Zhe; McGinnis, Sarah (Myers Education Press LLC, 2020)
The rise of high-stakes testing in New York and across the nation has narrowed and simplified what is taught, while becoming central to the effort to privatize public schools. However, it and similar reform efforts have met resistance, with New York as the exemplar for how to repel standardized testing and invasive data collection, such as inBloom. In New York, the two parent/teacher organizations that have been most effective are Long Island Opt Out and New York State Allies for Public Education. Over the last four years, they and other groups have focused on having parents refuse to submit their children to the testing regime, arguing that if students don't take the tests, the results aren't usable. The opt-out movement has been so successful that 20% of students statewide and 50% of students on Long Island refused to take tests. In Opting Out, two parent leaders of the opt-out movement--Jeanette Deutermann and Lisa Rudley--tell why and how they became activists in the two organizations. The story of parents, students, and teachers resisting not only high-stakes testing but also privatization and other corporate reforms parallels the rise of teachers across the country going on strike to demand increases in school funding and teacher salaries. Both the success of the opt-out movement and teacher strikes reflect the rise of grassroots organizing using social media to influence policy makers at the local, state, and national levels.